Let's talk about race - Lester, Julius; Barbour, Karen ([New York] : HarperCollins, 2005)
The author introduces the concept of race as only one component in an individual's or nation's "story."
"Amistad."
School Library Journal starred
Publisher's Weekly
Booklist
3.3
K-3
Keywords: United States -- Race relations -- Juvenile literature; Racism -- United States -- Juvenile literature; Race awareness -- United States -- Juvenile literature; Prejudices -- United States -- Juvenile literature; Lester, Julius -- Juvenile literature; Race awareness; Toleration; Racism; Lester, Julius; Race awareness; Toleration; Racism; Lester, Julius